Black-White Differences in Severe Maternal Morbidity and Site of Care - HOWELL, Elizabeth A. (Am J Obstet Gynecol, 2015)
BACKGROUND: For every maternal death, over 100 women experience severe maternal morbidity, a life threatening diagnosis or undergo a life-saving procedure, during their delivery hospitalization. Similar to racial/ethnic disparities in maternal mortality, black women are more likely to suffer from severe maternal morbidity than white women. Site of care has received attention as a mechanism explaining disparities in other areas of medicine. Data indicate that blacks receive care in a concentrated set of hospitals and these hospitals appear to provide lower quality of care. Whether racial differences in site of delivery contribute to observed black-white disparities in severe maternal morbidity rates is unknown. OBJECTIVE: To determine whether hospitals with high proportions of black deliveries have higher severe maternal morbidity and if such differences contribute to overall black-white disparities in severe maternal morbidity. STUDY DESIGN: We used a published algorithm to identify cases of severe maternal morbidity during deliveries in the Nationwide Inpatient Sample for 2010 and 2011. We ranked hospitals by their proportion of black deliveries into high black-serving (top 5%), medium black-serving (5% to 25% range) and low black-serving hospitals. We analyzed the risks of severe maternal morbidity for black and white women by hospital black-serving status using logistic regressions adjusted for patient characteristics, comorbidities, hospital characteristics, and within-hospital clustering. We then derived adjusted rates from these models. RESULTS: Seventy-four percent of black deliveries occurred at high and medium black-serving hospitals. Overall, severe maternal morbidity occurred more frequently among black than white women (25.8 vs. 11.8 per 1000 deliveries, p<.001); after adjusting for the distribution of patient characteristics and comorbidities, this differential declined, but remained elevated (18.8 vs. 13.3per 1000 deliveries respectively, p<.001). Women delivering in high and medium black-serving hospitals had elevated rates of severe maternal morbidity rates compared with those in low black-serving hospitals in unadjusted (29.4, 19.4, versus 12.2 per 1000 deliveries respectively, p<0 .001) and adjusted analyses (17.3, 16.5 vs. 13.5 per 1000 deliveries respectively, p<.001). Black women who delivered at high black-serving hospitals had the highest risk of poor outcomes. CONCLUSION: Most black deliveries occur in a concentrated set of hospitals, and these hospitals have higher severe maternal morbidity rates. Targeting quality improvement efforts at these hospitals may improve care for all deliveries and disproportionately impact care for black women.